Responsive Amorphous Photonic Structures of Spherical/Polyhedral Colloidal Metal–Organic Frameworks. Issue 13 (29th April 2019) - Bai, Ling; He, Yuheng; Zhou, Jiajing; Lim, Yun; Mai, Van Cuong; Chen, Yonghao; Hou, Shuai; Zhao, Yue; Zhang, Jun; Duan, Hongwei
Abstract: Amorphous photonic structures (APSs) with isotropic structural colors are of great promise for creating reflective full‐color displays or responsive colorimetric devices. However, there is a lack of guiding principles in developing stimuli‐responsive functional APSs, and the building blocks of APSs are still limited to spherical particles despite the increasing emergence of anisotropic functional particles. Moreover, current production of APSs, in particular high‐resolution APS patterns, is not fundamentally compatible with industrial manufacturing technologies, forming a major barrier toward their applications. Presented here is a proof‐of‐concept study on scalable fabrication of responsive APSs by colloidal assembly of spherical/polyhedral metal‐organic framework (MOF) particles on liquid‐permeable substrates. It is shown that infiltration assisted Mayer rod coating allows for rapid production of customized multicolored structural color patterns of MOF APSs by controlling liquid wetting/infiltration on the substrate with printed wax coatings. Small‐angle X‐ray scattering and optical measurements reveal the structural parameters of MOF APSs such as average nearest interscattering spacing and particle packing density, theoretically relating the optical properties and responsive color shifts of MOF APSs to factors affecting their scattering profile, which provides the guideline for the development of smart APS photonic devices via a wide spectrum of colloidal particles for diverse applications. Abstract : Amorphous photonic structures (APSs) of spherical/polyhedral colloidal metal–organic frameworks (MOFs) are prepared by scalable infiltration assisted rod‐coating technology. The optical properties and responsive color shifts of MOF APSs are elaborated by both theoretical calculation and experimental measurements, opening the avenue to developing smart photonic APS devices using a wide spectrum of isotropic/anisotropic colloidal particles.